Maria Biernacka. Szkic biograficzny - Koralewska, Ewa (Zeszyty Wiejskie, 2016)
The article presents the biography of Professor Maria Biernacka. She started her social-political activity in Małopolska Rural Youth Union, then she was a member of Rural Youth Union of Poland, since 1938 she belonged to the Polish People’s Party. In 1939 she completed a course of Rural Orkan University in Gacia near Przeworsk. In the years of German occupation she was a liaison officer and a distributor of conspiratorial press in the Headquarters of Peasants’ Battalions (1942–1943), and later she was an inspector of Rural Women’s Association in Warsaw area (1943–44). In 1944 she was an active member of BCh and LZK in Jasło region. After liberation she belonged to ZMW RP Wici and United Peasant Party. Since 1954 she was working in the Institute of the History of Material Culture of the Polish Academy of Sciences. She was an author of numerous monographs, studies and articles in the area of ethnography. She was very active in academic life of the Department of the History of Peasant Movement and the Museum of the History of Polish Peasant Movement. She was an ardent patriot, a well-known and highly regarded person. She died in Warsaw on April, 14 in 2007.